2021
DOI: 10.3390/ijms22189831
|View full text |Cite
|
Sign up to set email alerts
|

A Body of Circumstantial Evidence for the Irreversible Ectonucleotidase Inhibitory Action of FSCPX, an Agent Known as a Selective Irreversible A1 Adenosine Receptor Antagonist So Far

Abstract: In previous studies using isolated, paced guinea pig left atria, we observed that FSCPX, known as a selective A1 adenosine receptor antagonist, paradoxically increased the direct negative inotropic response to A1 adenosine receptor agonists (determined using concentration/effect (E/c) curves) if NBTI, a nucleoside transport inhibitor, was present. Based on mathematical modeling, we hypothesized that FSCPX blunted the cardiac interstitial adenosine accumulation in response to nucleoside transport blockade, prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…As a result of these two opposing effects, enhanced responses to low and medium agonist concentrations, furthermore reduced or unchanged responses to high agonist concentrations develop. This was observed in our previous studies performed in guinea pig and rat atria, using nitrobenzylthioinosine derivatives for adenosine transport blockade and applying adenosine as a metabolizable and transportable exogenous agonist (Karsai et al, 2006;Kiss et al, 2013;Erdei et al, 2018;Viczjan et al, 2021). This is also the case in the present study as regards the CBD-treated atria: we have found weaker responses to all CPA concentrations (Figure 1, left panel), while stronger responses to low and medium adenosine concentrations and unchanged responses to high adenosine concentrations (in comparison with the vehicle-treated atria) (Figure 1, right panel).…”
Section: Figuresupporting
confidence: 60%
See 3 more Smart Citations
“…As a result of these two opposing effects, enhanced responses to low and medium agonist concentrations, furthermore reduced or unchanged responses to high agonist concentrations develop. This was observed in our previous studies performed in guinea pig and rat atria, using nitrobenzylthioinosine derivatives for adenosine transport blockade and applying adenosine as a metabolizable and transportable exogenous agonist (Karsai et al, 2006;Kiss et al, 2013;Erdei et al, 2018;Viczjan et al, 2021). This is also the case in the present study as regards the CBD-treated atria: we have found weaker responses to all CPA concentrations (Figure 1, left panel), while stronger responses to low and medium adenosine concentrations and unchanged responses to high adenosine concentrations (in comparison with the vehicle-treated atria) (Figure 1, right panel).…”
Section: Figuresupporting
confidence: 60%
“…In a previous work, we found that the responsiveness of the myocardial A 1 adenosine receptor did not decrease in the time window of our ex vivo experiments ( Gesztelyi et al, 2004 ). Based on this, in our earlier studies dealing with the acute consequences of adenosine transport inhibition ( Karsai et al, 2006 ; Kiss et al, 2013 ; Erdei et al, 2018 ; Viczjan et al, 2021 ), no decrease in the (real) responsiveness of the A 1 adenosine receptor was considered. Consistent with this, the A 1 adenosine receptor was reported to be desensitized extremely slowly, even in the presence of significant amounts of full agonists for several weeks ( Willems et al, 2006 ; Mundell and Kelly, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After this “individualization”, the RRM’s model can simply be fitted to the corresponding distorted E/c curve ( Gesztelyi et al, 2004 ; Grenczer et al, 2010a ; 2010b ). In this paper (similarly to the recent ones: Szabo et al, 2019a ; Viczjan et al, 2021 ; 2022 ), this procedure will be referred to as individual regression. (Alternatively, this type of fitting can be called local regression, as opposed to global regression: Anjos et al, 2020 ; Spatial Data Science, 2024 ).…”
Section: Introductionmentioning
confidence: 99%